AC conductivity and phase transition of the BST–BFO ceramic doped with Yb. Issue 42 (26th September 2022) - Ben Abdessalem, M.; Chkoundali, S.; Oueslati, A.; Aydi, A.
Abstract : The homogeneity of the 0.8(Ba0.8 Sr0.2 )TiO3 –0.2(Bi0.85 Yb0.15 )FeO3 ceramic, prepared by a solid-state process, was studied and quantitatively analyzed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Abstract : The homogeneity of the 0.8(Ba0.8 Sr0.2 )TiO3 –0.2(Bi0.85 Yb0.15 )FeO3 ceramic, prepared by a solid-state process, was studied and quantitatively analyzed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). At ambient temperature, X-ray diffraction shows the existence of only one perovskite phase in the tetragonal structure with the space group P 4 mm . The thermal variations of (real part of the dielectric permittivity) for this composition show extended peaks with temperature; this broadening of the peaks can be attributed to the diffuse character of the transition. As the frequency increases, T m (temperature of maximum permittivity) moves at higher temperatures, and the maximum values of decrease. Moreover, the impedance spectra (− Z ′′ vs. Z ′) show the presence of two arcs of circles that have been modeled with an equivalent electrical circuit. The arcs of the circles centered under the real axis ( Z ) prove the Cole–Cole-type behavior. Each circle is associated with either the grain effect or grain boundaries. Electrical modulus analysis shows that the capacitance of the ceramic is enhanced, which is in good agreement with the results of complex impedance analysis. The AC conductivity complies with the universal power law. It disputes the modification of AC conductivity by adopting the Arrhenius-type of electrical conductivity. The temperature dependence of alternating current conductivity ( σ g ) and direct current conductivity ( σ DC ) confirms the existence of the ferroelectric–paraelectric phase transition.